Facial Asymmetry in a Crying Newborn: A Comparison of Two Cases and Review of Literature - Shreyas Arya; Sunil K. Jain; Carol J. Richardson (Case Reports in Pediatrics)
Facial asymmetry in a crying newborn can be due to a variety of different causes. Neonatal asymmetric crying facies (NACF) is a specific phenotype, which is often underrecognized. It is defined as asymmetry of the mouth and lips with grimacing or smiling, but a symmetric appearance at rest. NACF needs to be differentiated from complete facial palsy in a newborn, which can occur due to traumatic or developmental etiologies. Developmental causes can be present in isolation or may be a part of a recognized syndrome. While asymmetric lower lip depression may be seen in both conditions, complete facial palsy is also associated with upper and mid face deformities. We present a case of NACF and compare it to a case of facial palsy due to perinatal trauma. The purpose of this case series is to clarify some of the confusing nomenclatures and highlight the differences in the physical exam findings, diagnosis, and eventual prognosis of these cases.